Do old digs matter? The inspection of past excavation for new information, case Turku - Seppänen Liisa (Austria, 2022)
Turku, the oldest town of Finland, is in a key position when the excavations and methodological development of Finnish urban archaeology are discussed. The town has been a target of antiquarian research and archaeological excavations since the late 19th century. This activity has resulted in abundance of material as well as a diversity of documentation, which can be considered either as a problem or a possibility or both – depending on the aspects of the study and the attitude of the researcher.
The paper gives an overview to urban archaeology in Turku with the focus on the main junctures of methodological development and practices one has had to settle with in the past and present. It presents a case study, which included material from excavations of different kind, and estimates the value of old excavations for the new information. This study brought along a question, how the existing information could be processed in order to get a more holistic view of the past, and laid foundations for a new on-going project in which archaeological information is inventoried, analyzed, valued and represented. The project offers many challenges, and reservations regarding the amount of work are understandable and justified. However, the profitability of the project cannot be estimated before the work has been accomplished.
CHNT 19, 2014 – Proceedingsof the 19th International Conference on Cultural Heritage and New Technologies held in Vienna, Austria November 2014